PSAP IMPLEMENTATION ANALYSIS No. 6 IN DKI PROVINCIAL GOVERNMENT INVESTMENT 2014-2020 - bakar, abu (Jurnal Sosial Humaniora, 2023)
This research is about the application of PSAP No. 6 in the long-term investment of the DKI Jakarta local government with four objectives to know and understand 1) the investment profile of the DKI Jakarta government 2) what sectors the DKI Jakarta local government invests in, 3) how to invest in ownership and 4) how to apply PSAP No .6 in investment DKI Jakarta The research method used is descriptive method. The results of the study concluded that the investment profile within 9 years of the Jakarta provincial government’s investment increased and grew by 14.3 times, Capital investment in BUMD was not more than 3.7% of the total investment while 86.3% of capital investment was in third parties. The provincial government of DKI Jakarta invests in six business sectors and the largest sector is the construction sector by 35.9% and the transportation sector by 33.3% of the total investment. Investment ownership can be divided into three types, the first is 100% share ownership specifically for BUMD status companies as many as 5 companies, the second ownership between 80%-99.9% is capital investment in companies in the form of Limited Liability Companies and the third is capital investment between 0-30% Investment capital in private third parties as many as 7 companies. The local government has implemented PSAP No. 6 in the assessment of capital investment using the cost method and the equity method, but there are three irregularities in its application which causes the value of capital investment, one of which is an asset not to be seen in the Regional Government Financial Statements.